Features of the application of neuroprotective therapy for traumatic optic neuropathy in the clinical setting (Ukrainian Journal of Ophthalmology, 2025)
Background: The features of the application of neuroprotective therapy for traumatic optic neuropathy (TON) in the clinical setting are not known.Methods: Forty-nine TON patients (49 eyes) with MRI evidence of no compressive optic nerve injury were divided into group A (25 patients) and group B (24 patients) and underwent treatment. Patients of group A were treated with 1000 mg of pre-intravenous methylprednisolone daily for 3 days with subsequent gradual tapering of the dose. Patients of group B were treated with a 1000-mg methylprednisolone infusion daily for 3 days and bilateral electric phosphene stimulation (EPS) for 10 days.Results: We demonstrated in the clinical setting that, compared to steroid-only treatment, steroids plus EPS treatment for TON is characterized by greater improvements in (a) visual acuity, (b) selectivity of action depending on the ophthalmoscopic form of TON, and (c) atrophic processes in the axial bundle of the optic nerve. After combination treatment for TON, visual acuity improved by 0.6 to 0.8, and critical frequency of phosphene disappearance (CFPD) improved by 35 to 45 Hz. Compared with combined or inverse form of TON, ischemic form of TON is seen in the earlier period after the traumatic event. Steroids plus EPS treatment effect was greater in the last form than in the two former forms.Conclusion: Our steroids plus EPS treatment may be an alternative to conventional treatment (megadose steroid-only therapy) for TON in the clinical setting.
Keywords: traumatic optic neuropathy; neuroprotective therapy; electric phosphene stimulation